In-plane behavior of tuff masonry panels strengthened with FRP diagonal layout - Marcari, Giancarlo (2013)
The present paper deals with a quantitative analysis of the shear strength behavior of masonry panels strengthened with diagonal layout. The objective of the study is to progress towards understanding the shear strength contributions from masonry and FRP to the lateral resistance of strengthened panels. To this aim, relevant experimental results of monotonic shear-compression tests are analyzed. The local behavior of the reinforcement is investigated in terms of FRP strain profiles (i.e. the transferrable tension force within FRP), and its effects on the global response of the panels assessed. The experimental results show the effectiveness of the anchorage system in restraining the FRP at the anchored edges, avoiding premature failure due to FRP debonding. As a result, the specimens were allowed to develop their full lateral resistance. A truss model approach, combined with a proper masonry strength criterion for masonry is proposed and validated. A comparison between computed and experimental data confirms the validity of the procedure in view of practical applications and code recommendations.